Analysis of the Influence of Fiscal Decentralization, Dependency Ratio, and Ratio of Independence on the Human Development Index in East Region of Indonesia - Lilik Handayani; Seniorita; Samuel PD Anantajaya; Henky Hendrawan; Hendy Tannady (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The objectives of this study is to examine the influence of fiscal decentralization, dependency ratio and ratio of independence on human development index in east region of Indonesia. The method used in this research is quantitative research. This study used a sample of provinces in Indonesia. The samples used in this study were from 12 provinces in Eastern Indonesia, namely, West Nusa Tenggara, East Nusa Tenggara, North Sulawesi, Central Sulawesi, South Sulawesi, Southeast Sulawesi, Gorontalo, West Sulawesi, Maluku, North Maluku, Papua, and West Papua. In this study, we used secondary data types with the time period 2010-2019. In this study, all variable data units are percent. The data used in this study is secondary data in the form of panels, which is a combination of cross-sectional data and time series data. The conclusion of this study is that the degree of fiscal decentralization has an effect, but not significantly, and shows a negative relationship to the human development index. This shows that if there is an increase in the degree of fiscal decentralization, it will reduce the human development index.